Pengaruh Independensi Komite Audit dan Kepemilikan Keluarga terhadap Manajemen Laba di Perusahaan Bursa Efek Indonesia - Valeria; Karina, Ria (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to examine how audit committee independence and family ownership affect earnings management. This study was prepared by considering the prevalence of earnings management cases in Indonesian companies. Earnings management is the act of a company manipulating related company profits obtained in one period in order to gain profits. In this study, the audit committee's independence and family ownership are the independent variables, whereas earnings management is the dependent variable. Family ownership also acts as a moderating variable. There are 11 other control variables included in support of the research conducted. The annual reports and financial statements of non-banking companies listed on the Indonesia Stock Exchange were used as secondary data sources for this study. This research uses Multiple Regression Analysis utilizing the SPSS software. According to the study’s findings, audit committee independence has no significant relationship to earnings management, while family ownership is significantly positively correlated with earnings management. Besides that, family ownership is not able to moderate audit committee independence on earnings management. Thus, it may be said that the family ownership structure of companies may influence earnings management practices in Indonesian public non-banking companies.